2023
DOI: 10.1039/d2an01757a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent strip sensor for rapid and ultrasensitive determination of fluoroquinolones in fish and milk

Abstract: The synthetic antibiotics fluoroquinolones are popular due to their good antibacterial performance and low price, but the risk to human health caused by their residues has attracted great attention. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…1b). 28 Briefly, 6.99 mg of CLZH and 8.28 mg of N -hydroxysuccinimide (NHS) were dissolved in 400 μL of N , N -dimethylformamide (DMF) and stirred for 15–20 min. Then, 13.75 mg 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) dissolved in 50 μL of 4-morpholineethanesulfonic acid solution (MES, 0.1 M, pH 5.5) was slowly added and the reaction was stirred at room temperature for 6 h. Next, the mixture was mixed with 8 mg KLH dissolved in 3 mL of carbonate buffer (CB, 0.1 M, pH 9.6).…”
Section: Methodsmentioning
confidence: 99%
“…1b). 28 Briefly, 6.99 mg of CLZH and 8.28 mg of N -hydroxysuccinimide (NHS) were dissolved in 400 μL of N , N -dimethylformamide (DMF) and stirred for 15–20 min. Then, 13.75 mg 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) dissolved in 50 μL of 4-morpholineethanesulfonic acid solution (MES, 0.1 M, pH 5.5) was slowly added and the reaction was stirred at room temperature for 6 h. Next, the mixture was mixed with 8 mg KLH dissolved in 3 mL of carbonate buffer (CB, 0.1 M, pH 9.6).…”
Section: Methodsmentioning
confidence: 99%
“…Compared with colloidal gold-labeled immunochromatography strip assays (ICSAs), the novel immunosensors need to be further validated for practical application in the market, although they have the advantages of low manufacturing cost, simple storage conditions, no/minimal sample preparation, and immediate operability [12,13]. ICSAs offer a simpler and more convenient solution, and previous studies demonstrated that this method is effective in detecting fluoroquinolones immunosorbent [14][15][16][17][18][19][20][21][22][23][24][25]. ICSAs' principal advantage over other analytical methods is that it does not require specialized skills, expensive and complex instrumentation, all-inclusive, can provide results in a timely manner (5-10 min), and can easily yield both qualitative and quantitative results for a wide range of analytes.…”
Section: Introductionmentioning
confidence: 99%
“…The ICS assay generally works in qualitative or semiquantitative analysis in addition to single target detection from a single sample due to the substantial interference with food matrices and colored samples. [18][19][20] As complementary or alternative analytical techniques, biosensors which comprise a biological recognition element (such as an antibody, receptor, enzyme, etc.) and a transducer (converting the recognition event into a measurable signal) have elicited signicant interest in on-site detection of antibiotic residues in various matrices because of their superiorities of high sensitivity and selectivity, rapid detection, and easy operation.…”
Section: Introductionmentioning
confidence: 99%
“…The ICS assay generally works in qualitative or semi-quantitative analysis in addition to single target detection from a single sample due to the substantial interference with food matrices and colored samples. 18–20…”
Section: Introductionmentioning
confidence: 99%